UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII MELALUI MODEL PEMBELAJARAN GROUP TO GROUP EXCHANGE (GGE) - Febrinda, Febrinda (Epsilon: Jurnal Pendidikan Matematika, 2020)
Abstract: Education has a very important role to ensure the development and survival of a nation. Mathematics learning in class VII Mts Al Khairiyah Bandar Lampung is still one-way, this causes students' mathematics learning outcomes in class VII to be less than optimal, students still find it difficult to learn and understand mathematics, students lack interest and are not actively involved in learning mathematics, and student activity in learning is still not good. The purpose of this study was to determine the increase in student activity and learning outcomes using the Group to Group Exchange (GGE) learning model for seventh grade students in the even semester of MTs Al Khairiyah Bandar Lampung for the 2020/2021 school year. This research is a Classroom Action Research (CAR). The research was carried out in 2 cycles with 8 face-to-face meetings. During the study, data obtained on the increase in student activity from cycle 1 to cycle 2, namely from 50% to 76.7%, while the percentage of classical learning outcomes in cycle 1 was 56% and cycle 2 was 81%. This increase in activity and learning outcomes proves that the use of the Group to Group Exchange (GGE) learning model can increase students' activities and learning outcomes in mathematics.